Revealing the ultrastructure of the membrane pores of intact Serratia marcescens cells by atomic force microscopy - Lin, Yu-Chun (Heliyon, 2019)
This study aimed to characterize the surface ultrastructure of intact Serratia marcescens cells under physiological conditions. Topographic information of membrane pores of the cells was obtained by atomic force microscope (AFM). Three types of membrane pores (CH-1-Pore A, CH-1-Pore B and CH-1-Pore C) were observed and the spatial arrangements of membrane-spanning subunits in membranes were defined. High-resolution images revealed that the doughnut-shaped structures of CH-1-Pore A and CH-1-Pore B were composed of six-to-eight and four transmembrane subunits. The inverted teepee-shaped structure of CH-1-Pore C was segmented into two transmembrane subunits straddling a single funnel-like pore. This study, to the best of authors' knowledge, represents the first direct characterization of the surface ultrastructure of the membrane pores of Serratia marcescens CH-1 cells at the nanometer scale and offers new prospects of mapping membrane pores on intact prokaryotic cells.